Deep Learning and Neural Networks 2020
DOI: 10.4018/978-1-7998-0414-7.ch048
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of Electricity Demand by Hybrid ANN-PSO Models

Abstract: Developing economies need to invest in energy projects. Because the gestation period of the electric projects is high, it is of paramount importance to accurately forecast the energy requirements. In the present paper, the future energy demand of the state of Tamil Nadu in India, is forecasted using an artificial neural network (ANN) optimized by particle swarm optimization (PSO) and by Genetic Algorithm (GA). Hybrid ANN Models have the potential to provide forecasts that perform well compared to the more trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…PSO combines the characteristics of both the evolution strategies (ES) and GA and it has more stable convergence features than other stochastic techniques. (see Zuperl et al, 2007;Phanthuna et al, 2013;Anand and Suganthi, 2020). Succinctly, we used this technique due to its advantage in multi-objective optimization, the ability to reduce the cost of estimation and also checks the priority of each variable via permutation and combination.…”
Section: Methodsmentioning
confidence: 99%
“…PSO combines the characteristics of both the evolution strategies (ES) and GA and it has more stable convergence features than other stochastic techniques. (see Zuperl et al, 2007;Phanthuna et al, 2013;Anand and Suganthi, 2020). Succinctly, we used this technique due to its advantage in multi-objective optimization, the ability to reduce the cost of estimation and also checks the priority of each variable via permutation and combination.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they validated its effectiveness using the Electric Reliability Council of Texas (ERCOT). Anand et al [25] deployed an ANN-based PSO model to forecast future energy demand for a state of India. Both particle swarm optimization (PSO) and Genetic algorithm (GA) were developed in linear and quadratic forms, and the hybrid ANN models were applied to different series.…”
Section: Related Workmentioning
confidence: 99%
“…Fan et al [17] used a multi-layer perception neural network prediction model for carbon prices to explain their nonlinearity. However, Anand and Suganthi [18] suggested that a single prediction approach could not produce better performance all the time because of sampling variation, structural changes, and model uncertainty. Therefore, hybrid models have been proposed to overcome the drawbacks of single models to improve the forecast accuracy of carbon prices.…”
Section: Literature Reviewmentioning
confidence: 99%